Leukemia From Biology to Clinic - Guenova, Margarita; Balatzenko, Gueorgui (IntechOpen, 2023)
Medical professionals and researchers in the field of leukemias are faced with the need to continuously update their knowledge in a wide range of areas, ranging from fundamental molecular processes and mechanisms to a thorough understanding of clinical features and modern approaches to achieve maximum therapeutic results. This book does not have the ambition to present comprehensively the problems of leukemias, but it is an attempt to acquaint the audience of specialists involved in clinical management and experimental research with some modern advances and concepts in the three main directions: biology, clinical presentation and treatment. The biological aspects of the origin, development and therapy resistance of leukemias are within the scope of the first section. Comprehensive and concise information on the clinical assessment and treatment of leukemia patients is provided, as well as on some specific interdisciplinary clinical scenarios such as leukemic retinopathy, in the second section. Finally, challenges, current standards and recent advances in the therapy of acute leukemias comprise the third section of the book.